2021
DOI: 10.1073/pnas.2017225118
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide is neuroprotective in Alzheimer’s disease by sulfhydrating GSK3β and inhibiting Tau hyperphosphorylation

Abstract: Alzheimer’s disease (AD), the most common cause of dementia and neurodegeneration in the elderly, is characterized by deterioration of memory and executive and motor functions. Neuropathologic hallmarks of AD include neurofibrillary tangles (NFTs), paired helical filaments, and amyloid plaques. Mutations in the microtubule-associated protein Tau, a major component of the NFTs, cause its hyperphosphorylation in AD. We have shown that signaling by the gaseous molecule hydrogen sulfide (H2S) is dysregulated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(123 citation statements)
references
References 82 publications
2
121
0
Order By: Relevance
“…Many of the biochemical characteristics of H 2 S signaling that provide cytoprotective effects, such as persulfidation of signaling proteins, can be accomplished with thiosulfate instead. For example, a study by Giovinazzo et al [ 99 ] showed that H 2 S donor molecule GYY4137 inhibits Tau hyperphosphorylation by persulfidation of kinase GSK3β, ultimately ameliorating cognitive and motor deficits in Alzheimer’s disease. STS, as we previously mentioned, has been shown to trigger persulfidation reactions in the sulfur oxidation pathway [ 37 ] and in the Nrf2 signaling pathway [ 95 ].…”
Section: Future Directionmentioning
confidence: 99%
“…Many of the biochemical characteristics of H 2 S signaling that provide cytoprotective effects, such as persulfidation of signaling proteins, can be accomplished with thiosulfate instead. For example, a study by Giovinazzo et al [ 99 ] showed that H 2 S donor molecule GYY4137 inhibits Tau hyperphosphorylation by persulfidation of kinase GSK3β, ultimately ameliorating cognitive and motor deficits in Alzheimer’s disease. STS, as we previously mentioned, has been shown to trigger persulfidation reactions in the sulfur oxidation pathway [ 37 ] and in the Nrf2 signaling pathway [ 95 ].…”
Section: Future Directionmentioning
confidence: 99%
“…A common characteristic reported in the literature, found in even unrelated ND, is the loss/decrease of CSE which has been observed in human samples of Parkinson's, Huntington's, Alzheimer, and spinocerebellar ataxia 3 diseases, as well as in corresponding animal disease models (Vandiver et al, 2013 ; Paul et al, 2014 ; Snijder et al, 2015 ; Giovinazzo et al, 2021 ). A global decrease of protein persulfidation has also been observed for the latter three diseases (Snijder et al, 2015 ; Zivanovic et al, 2019 ; Giovinazzo et al, 2021 ).…”
Section: Cse → H 2 S → Pssh Axis In Neurodegenerationmentioning
confidence: 87%
“…A common characteristic reported in the literature, found in even unrelated ND, is the loss/decrease of CSE which has been observed in human samples of Parkinson's, Huntington's, Alzheimer, and spinocerebellar ataxia 3 diseases, as well as in corresponding animal disease models (Vandiver et al, 2013 ; Paul et al, 2014 ; Snijder et al, 2015 ; Giovinazzo et al, 2021 ). A global decrease of protein persulfidation has also been observed for the latter three diseases (Snijder et al, 2015 ; Zivanovic et al, 2019 ; Giovinazzo et al, 2021 ). Besides a general protection, persulfidation could also represent a redox switch mechanism by which protein structure and/or function might be affected, and the search of these particular targets may pave the way to more targeted drug design toward ND therapeutics.…”
Section: Cse → H 2 S → Pssh Axis In Neurodegenerationmentioning
confidence: 87%
See 2 more Smart Citations